Electrically tunable evanescent mode half-mode substrate-integrated- waveguide resonators (2012)
Electrically tunable evanescent mode half mode substrate integrated waveguide (HMSIW) resonators are implemented for S band applications. An HMSIW loaded with a complementary split ring resonator (CSRR) achieves forward electromagnetic wave transmission below the characteristic waveguide cutoff frequency due to evanescent wave amplification. A variable capacitor connected to one of the conductors of the CSRR changes its effective capacitance to ground, resulting in frequency tuning of the resonator. Three different configurations are investigated with a varactor diode connected between the ground and three different contact points of the CSRR. The external Q factor is slightly affected by the frequency tuning. More than 15% tunability is achieved around 3.4 GHz. Full wave structure simulation results are in good agreement with those of measurement. © 2006 IEEE.